Ultrasound-guided transversus thoracic muscle plane-pectoral nerve block for postoperative analgesia after modified radical mastectomy: a comparison with the thoracic paravertebral nerve block - Ying Zhao; Weilin Jin; Peng Pan; Shuquan Feng; Danyun Fu; Junyan Yao (Perioperative Medicine, 2022)
Abstract Background Modified radical mastectomy (MRM) is the most effective and common type of invasive surgery for breast cancer. However, it causes moderate to severe acute pain and even lasts for a long postoperative period. Transversus thoracic muscle plane-pectoral nerve block (TTP-PECS) is a novel and promising interfacial plane block which can provide analgesia for MRM while thoracic paravertebral nerve block (TPVB) is also widely used for this purpose. This study compared the postoperative analgesia between the ultrasound-guided TTP-PECS and TPVB in patients undergoing MRM. Methods In this randomized controlled trial, eighty female breast cancer patients undergoing unilateral MRM with sentinel lymph node dissection (SLND) and axillary dissection (ALND) were enrolled. Patients were randomized to receive either ultrasound-guided TTP-PECS (TTP-PECS group, n = 40) or TPVB (TPVB group, n = 40) with 0.5% ropivacaine 30 ml. Evaluated variables included 24 h postoperative total PCA fentanyl consumption, including PCA background consumption and PCA press consumption (per bolus dosage multiply by the effective pressing times), and intraoperative fentanyl consumption, as well as postoperative flurbiprofen axetil requirement, duration of analgesia, blocking area, pain intensity at rest and during activity, ability to reduce the inflammatory response, and the quality of recovery 40 (QoR-40) score of patients. Results Compared with the TPVB, the main blocking area was T 2–T 6 in the TTP-PECS group, which was more suitable for the MRM. TTP-PECS has a longer analgesia duration than TPVB; 24 h postoperative total PCA fentanyl consumption, especially the PCA press consumption, and the postoperative flurbiprofen axetil requirement were decreased in the TTP-PECS group than those in the TPVB group. Furthermore, the VAS scores at rest and during activity and inflammatory response were lower in the TTP-PECS group compared with the TPVB group at 12 h postoperatively. Finally, the total QoR-40 score, especially for the scores of pain; emotional state; and patient support were better in the TTP-PECS group. Conclusion Compared with the TPVB, TTP-PECS can provide better postoperative analgesia in patients undergoing MRM, simultaneously reduce the inflammatory response, and prompt early recovery. These results suggest that TTP-PECS is an attractive alternative to TPVB for postoperative analgesia of modified radical mastectomy.